Effect of solution treatment on the formability and part performance of IN718 sheet material. Issue 4 (2nd October 2018) - Prasad, K. S.; Panda, S. K.; Kar, S. K.; Murty, S. V. S. N.; Sharma, S. C.
ABSTRACT: IN718 sheets were separately solution treated to two different temperatures i.e. 970°C (HT970) and 1070°C (HT1070). Due to higher solution treatment temperature (1070°C), the microstructure altered considerably i.e. grain size increased, volume fraction of both strengthening phases ( ) obliterated from the matrix ( ), and delta phase ( ) dissolved. Further, both the heat-treated samples were deformed using limiting dome height (LDH) setup along different strain paths ranging from tension-compression to tension-tension deformation modes. It was observed that all the samples failed catastrophically without any significant hint of necking, and hence, fracture forming limit diagrams (FFLD) were estimated. It was found that the FFLD of HT1070 was marginally higher in comparison to that of HT970 material. The formability in terms of LDH, crack location and strain evolution for biaxially deformed cup was predicted successfully by finite element model incorporating Hills-48 plasticity theory. The results showed higher LDH with well-developed strain distribution in case of HT1070 material in comparison to that of HT970 material. However, the surface topography of biaxially stretched cup showed 116% increase in roughness for HT1070 material. The higher intensity of Brass and lower intensity of Cube components were responsible for higher surface roughness in case of HT1070 material.